2012
DOI: 10.1590/s1809-29502012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da coluna lombar e torácica nas situações com salto alto e com os pés descalços com o instrumento arcômetro

Abstract: RESUMO | O salto alto há muitos anos tem sido um grande aliado das mulheres, tornando-se uma ferramenta fundamental em seu dia a dia. Contudo, a utilização indiscriminada, seja do ponto de vista da frequência de utilização ou da altura do salto, pode trazer prejuízos para a saúde do corpo, que, a busca do melhor equilíbrio, pode desencadear alterações da postura, trazendo problemas para os pés e para a coluna vertebral. Os objetivos deste estudo foram: identificar a postura das curvaturas das colunas vertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…Equivalent results were found in the literature for gait evaluation. In Minossi's study (2011) 5 , spinal angulation did not present significant differences when comparing gait with and without heels (9 cm). On the other hand, Baaklini et al (2017) 19 reported a decrease in lumbar thoracic spine angles when comparing gait with low and high heels (4cm and 10cm, respectively).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Equivalent results were found in the literature for gait evaluation. In Minossi's study (2011) 5 , spinal angulation did not present significant differences when comparing gait with and without heels (9 cm). On the other hand, Baaklini et al (2017) 19 reported a decrease in lumbar thoracic spine angles when comparing gait with low and high heels (4cm and 10cm, respectively).…”
Section: Discussionmentioning
confidence: 77%
“…Pegoretti et al (2005) 4 , with participants who walked on an ergometric treadmill, report that lumbar lordosis straightened progressively as heel height increased. On the other hand, Minossi et al (2012) 5 , when analyzing young participants in orthostatic position, found no significant differences for thoracic and lumbar angles in upright posture when wearing 9cm heels compared to when barefoot.…”
Section: Introductionmentioning
confidence: 97%
“…Devido sua complexidade funcional, as dores provenientes da coluna vertebral são as principais causas de dores crônicas na população em geral, tendo sido observado em adultos da região Sul do Brasil uma prevalência de cerca de 63% ao longo de um ano, sendo a região lombar responsável pela maior parte dos casos (40%), seguida pela região torácica (36%) e cervical (24%) 1 , fato também observado em estudantes 2 . Segundo Briggs et al (2009) 3 a prevalência de pessoas com dor na região torácica possui uma alta variação, em torno de 3 a 55%.…”
Section: Introductionunclassified
“…8 Thus, techniques for assessing noninvasive spine have been proposed as they are considered to be of low complexity and low cost. In this context, instruments such as the photogrammetry associated to softwares 9 the arcometer 10 and the flexicurve 8 have driven to new researches on postural assessment in order to promote the use of these low complexity systems. The flexicurve already well documented in the literature, consists of a straight ruler, made of plastic-coated metal, which is molded on the back of the individual in order to illustrate the outline of the vertebral column, allowing a quick and cheap assessment of the curvatures of the vertebral column in the clinical environment, and also in study fields or with a big population.…”
Section: Introductionmentioning
confidence: 99%